Physical Activity Capacity Assessment of Patients With Chronic Disease and the 1-Minute Sit to Stand Test: Is There an Interest? - Allado, Edem; Poussel, Mathias; Albuisson, Eliane; Paysant, Jean; Temperelli, Margaux; Hily, Oriane; Moussu, Anthony; Benhajji, Noura; Gauchard, Gerôme; Chenuel, Bruno (Frontiers in Sports and Active Living, 2022)
Objective: This study aimed to evaluate the efficacy of the 1-minute Sit to Stand test (1MSTS) to determine physical activity capacities for patients with chronic disease. Methods: For this cross-sectional study, we studied fifty patients with chronic disease and no beta-blocker treatment. They systematically performed a cardiopulmonary exercise test to determine maximal oxygen uptake (V’O2max). We considered two groups of patients based on the results of the functional evaluation of exercise performance: (1) No limitation in exercise performance (V’O2max greater or equal to 80% of the theoretical reference) and (2) limited exercise performance (V’O2max less than 80% of the theoretical value). All patients also received an IMSTS on the same day. Results: We found 22 (44.0%) patients with normal exercise capacity and 28 (56.0%) patients with limited exercise performance. In this sample, mean 1MSTS repetitions were 27.1 (7.1) and 25.2 (8.7), respectively. There were no significant differences between the two groups for repetition and Borg Scale end test. The correlation between V’O2max measured during the exercise test and 1MSTS repetitions displayed a positive slope (r =0.401 – p=0.004). Conclusion: This study demonstrated a poor relationship between 1MSTS and V’O2max for patients with chronic disease. 1MSTS did not permit the precise determination of physical activity capacities in this sample.